ANALYSIS OF THE SYSTEM OF DRIVING SCHOOLS IN SELECTED EU COUNTRIES AND THE SLOVAK REPUBLIC (Perner's Contacts, 2022)
According to figures provided by the European Commission, more than 20,000 people die each year when traveling in the European Union (Press release European Commission, 2021). In 2019, the EU average of road accidents was 51 deaths per million inhabitants, with significant differences between low and high accident rates. In the Slovak Republic, drivers with a driving experience of up to 5 years (approximately 25%) cause fatal accidents every year, while drivers who belong to this group make up only 11.6% of all drivers (Statistical overviews of the agenda of traffic accident in the Slovak Republic and complete statistics Ministry of the Interior of the Slovak Republic, 2022). One of the causes of this condition can be sought directly in driving schools. The main goal of the paper is to analyse the system of driving schools based on selected criteria in selected thirteen EU countries (Bulgaria, Czechia, Denmark, Finland, the Netherlands, Croatia, Lithuania, Latvia, Germany, Poland, Romania, Slovenia and Sweden), which show differences in numbers. People killed in traffic accidents and compare them with the system of driving schools in the Slovak Republic. The paper also looks for a link between the number of fatal traffic accidents in a given country and the driving school system.